Intensive chemotherapy in children with acute lymphoblastic leukemia. Interim analysis in a referral center in Colombia - Ángela María Trujillo (Revista de la Facultad de Medicina, 2016)
Background: Acute lymphoblastic leukemia is the most common cancer in children. In developed countries, overall survival rates are around 80%, while in developing countries, survival rate is much lower due to high rates of relapse, and abandonment and complications arising from the disease treatment. Objectives: To assess induction mortality, relapse and treatment abandonment. To describe the most frequent side effects of chemotherapy. To evaluate survival rates of patients and compare the findings found in this study with the existing literature. Material and methods: A retrospective cohort study was conducted on patients aged 1 to 18 with acute lymphoblastic leukemia, who received treatment under the BFM ALL IC 2009 protocol at Fundación Hospital La Misericordia (HOMI), from November 2012 to December 2014.Results: 119 patients were included. Death occurred in two cases during induction (1.67%) and in nine (7.7%) due to treatment, all of them caused by infection/sepsis and in complete remission. Six patients abandoned treatment (5%), while seven relapses occurred (5.9%). All patients experienced some type of side effect related to chemotherapy, the most frequent being febrile neutropenia (41.2%) and grade 3-4 infections (15.8%). Overall survival and event-free survival rates were 79.9% and 73.3%, respectively. Conclusions: Evaluating complications of treatment and death allows adopting measures and strategies to reduce such complications.